How a Therapy Dog May Inspire Student Literacy Engagement in the Elementary Language Arts Classroom (LEARNing Landscapes, 2009)
In this article, I discuss theoretical possibilities for the inclusion of therapy dogs in the elementary language arts classroom, particularly which may inspire students otherwise reluctant to engage in literacy activities. I incorporate Guthrie and colleagues’ work in engagement into research in Animal Assisted Therapy with children to posit a revised theory of engagement.
Keywords: literacy; animal assisted theraphy; theraphy dog; engagement; elementary; languag earts classroom; literacy activities